Agroindústria familiar, desenvolvimento rural e sustentabilidade - Passini, João José (2020)
Brazilian agriculture is still very heterogeneous, even after five decades of the introduction of the Green Revolution. In regions markedly integrated with international markets, such as the western region of Paraná, with a strong presence of systems based on agricultural commodities, there is also agriculture with a strong presence of diversified production systems based on family farming. Farmers have fully implemented the option offered by the Green Revolution translated, in Brazil, as a process of modernization of agriculture, that is, extreme technical specialization. These family farmers use the diversification of their livelihoods as a survival strategy, among which is the transformation of agricultural production into the family production unit, in products made in rural agro-industries, which have a great capacity to add value to products and job creation. In this context, the objective of this work was to study the influence of rural agro-industries on the degree of sustainability of family agricultural production units (UPF) in the West of Paraná, through the dimensions of natural, physical, financial, social and human sustainability. The importance of the rural family agro-industry in the social and economic context of family farming in Brazil was also studied. The research was carried out with a group of diversified UPFs in the western region of Paraná - Brazil, analyzing their strategies, especially the transformation of products in rural agro-industries and how this strategy contributes to the expansion of the sustainability of these systems. The sustainable livelihood approach was used. To obtain the empirical data, two questionnaires were applied to the UPFs. Data analysis was carried out using the Propensity Score Matching econometric method to estimate the effect of the adoption of rural agro-industries on sustainability indicators. In addition, two tools were used, descriptive statistics and qualitative analysis of open responses. The analysis of data from the Agricultural Censuses of 2006 and 2017 showed that family rural agro-industries were present in 17% of the total of agricultural establishments in Brazil, expressing their importance as an income diversification strategy, especially considering the average contribution to the UPFs monetary income. The research also showed that there is a positive relationship between the existence of agro-industry in UPFs in the western region of Paraná in terms of sustainability of the financial, physical and environmental dimensions, and that there is no difference in the social and human dimensions, between the groups studied with and without agro-industries.